One Year On : Review of Country Initiatives in Public Participation in the Roll Out of Devolution - Nizam, Rabya; Muriu, Abraham Rugo (World Bank Group, Washington, DC, 2015)
The roll-out of devolution has been formally underway since March 2013 when county governments were established under the 2010 Constitution. The period under review is April 2013 to June 2014, which enables observations of public engagement in preparation of the 2013-2014 county budgets (between April-June 2013) and the 2014-2015 county budgets (between September 2013-June 2014). This paper reviews initial county initiatives on public participation and possible interventions to improve the overall design and implementation of participatory systems going forward.